Hantu Populer di Film Indonesia - Zein Muffarih Muktaf (Jurnal Komunikasi, 2008)
Ghost myth is popular in Indonesia. Myth specter appears from the primitive to the modern era. Ghost phenomenon increasingly popular after the movies began to spook a lot of pop. There are several factors that emerged a large number of ghost movies in Indonesia today. One of them is the Eastern faith that believes "naturalism" as a faith, capitalism factor, technology and human progress. Ghost has been commodified into beneficial asset. Thus, myth was distorted by capital accumulation. This phenomenon eventually lead to the identity crisis in the community, especially young people as the main target of these movies.